Risk Management and the Relationship with Performance of Listed Insurance Organizations - Fu, Cong (2014)
This paper discusses the risk management in the insurance industry and test the relationship between organizational performance and risk and other financial factors. The sample is collected all over the world with latest 10 years data. The risk management has five stages, which are risk identification, risk assessment, decision making, strategy implementation and risk monitoring. Dependent variable, which is organizational performance is defined as ‘earning before intest and tax’, and the independent variables contains risk, which is indicated by value of enterprise risk management, tangibility, liquidity, growth rate, insurance leverage, firm size and financial leverage .And three panel data regression is employed, which are overall panel data regression, life and health insurance regression and overall insurance with financial crisis dummy variable regression. The result is that, in the overall regression, enterprise risk management is negative, while insurance leverage and firm size are positive; in the life and health insurance sample, enterprise risk management is positive, but firm size, insurance leverage and tangibility are negative to performance. Lastly, in the regression with dummy variable, the financial leverage and tangibility is significant to the organizational performance when the financial crisis occurred. Key words: risk management, enterprise risk management, level of leverage